Laparoscopic Pancreaticoduodenectomy Versus Conventional Open Approach for Patients With Pancreatic Duct Adenocarcinoma: An Up-to-Date Systematic Review and Meta-Analysis - Feng, Qingbo; Liao, Wenwei; Xin, Zechang; Jin, Hongyu; Du, Jinpeng; Cai, Yunshi; Liao, Mingheng; Yuan, Kefei; Zeng, Yong (Frontiers in Oncology, 2021)
Background To compare perioperative and oncological outcomes of pancreatic duct adenocarcinoma (PDAC) after laparoscopic versus open pancreaticoduodenectomy (LPD versus OPD), we performed a meta-analysis of currently available propensity score matching studies and large-scale retrospective cohorts to compare the safety and overall effect of LPD to OPD for patients with PDAC. Methods A meta-analysis was registered at PROSPERO and the registration number is CRD42021250395. PubMed, Web of Science, EMBASE, Cochrane Central Register, and ClinicalTrials.gov databases were searched based on a defined search strategy to identify eligible studies before March 2021. Data on operative times, blood loss, and 30 days mortality, reoperation, length of hospital stay (LOS), overall morbidity, Clavien-Dind≥3 complications, postoperative pancreatic fistula (POPF), blood transfusion, delayed gastric emptying (DGE), post-pancreatectomy hemorrhage (PPH), and oncologic outcomes (R0-resection, lymph node dissection, overall survival, and long-term survival) were subjected to meta-analysis. Results Overall, we identified 10 retrospective studies enrolling a total of 11,535 patients (1,154 and 10,021 patients underwent LPD and OPD, respectively). The present meta-analysis showed that there were no significant differences in overall survival time, 1-year survival, 2-year survival,30-day mortality, Clavien-Dindo≥3 complications, POPF, DGE, PPH, and lymph node dissection between LPD and OPD group. Nevertheless, compared with the OPD group, LPD resulted in significantly higher rate of R0 resection (OR:1.22; 95% CI 1.06–1.40; p＝0.005), longer operative time(WMD: 60.01 min; 95% CI 23.23-96.79; p=0.001), lower Clavien–Dindo grade ≥ III rate (p = 0.02), less blood loss (WMD: −96.49 ml; 95% CI −165.14 to – 27.83; p =0.006), lower overall morbidity rate (OR: 0.65; 95% CI 0.50 to 0.85; p =0.002) ,shorter LOS (MD = - 2.73; 95% CI – 4.44 to – 1.03; p=0.002) ,higher 4-year survival time(p = 0.04), 5-year survival time (p = 0.001) and earlier time to starting adjuvant chemotherapy after surgery (OR -10.86; 95% CI -19.42 to -2.30; P=0.01). Conclusions LPD is a safe and feasible alternative to OPD for patients with PDAC. And compare to OPD, LPD seemed to provide a similar OS.